Relationship Between Body Mass Index, Selective Voluntary Motor Control and Functional Independence in Children With Cerebral Palsy - Alaa AL-Nemr (Iranian Rehabilitation Journal)
Objectives: This study detects the relationship between body mass index (BMI), selective voluntary motor control (SVMC) and functional independence in children with spastic diplegic cerebral palsy (CP). Methods: A total of 84 children with spastic diplegic CP (levels II and III of gross motor function classification system [GMFCS]), aged 6-9 years with a mean age of 7.09±0.68 participated in this correlational study. BMI, selective control assessment of the lower extremity and pediatric functional independence measure (WEE FIM) were used to assess BMI, SVMC and functional independence, respectively. Results: The data demonstrated the presence of a positive strong significant correlation between selective control assessment of the lower extremity and WEE FIM. On the other hand, there was a negative, significant correlation between WEE FIM and BMI. In addition, a negative moderate considerable correlation between BMI and selective control assessment of the lower extremity was detected Discussion: Functional independence is significantly correlated with BMI and SVMC in children with spastic diplegic CP. BMI and SVMC are major factors that influence functional independence in these children. So, they are highly recommended to be part of the evaluation of the functional independence of children with spastic diplegia in clinical settings and research.